Near infrared two-photon-excited and -emissive dyes based on a strapped excited-state intramolecular proton-transfer (ESIPT) scaffold. Issue 10 (9th February 2018) - Suzuki, Naoya; Suda, Kayo; Yokogawa, Daisuke; Kitoh-Nishioka, Hirotaka; Irle, Stephan; Ando, Akihiro; Abegão, Luis M. G.; Kamada, Kenji; Fukazawa, Aiko; Yamaguchi, Shigehiro
Abstract : Strapped acceptor–π–donor–π–acceptor type fluorophores exhibit intense near infrared emission, together with near infrared two-photon absorption. Abstract : Fluorophores that can undergo excited-state intramolecular proton transfer (ESIPT) represent promising scaffolds for the design of compounds that show red-shifted fluorescence. Herein, we disclose new near infrared-emissive materials based on a dialkylamine-strapped 2, 5-dithienylpyrrole as an ESIPT scaffold. The introduction of electron-accepting units to the terminal positions of this scaffold generates acceptor–π–donor–π–acceptor (A–π–D–π–A) type π-conjugated compounds. Following the ESIPT, the electron-donating ability of the core scaffold increases, which results in a substantially red-shifted emission in the NIR region, while increasing the oscillator strength. The electron-accepting units play a vital role to achieve intense and red-shifted emission from the ESIPT state. The strapped dialkylamine chain that forms an intramolecular hydrogen bond is also essential to induce the ESIPT. Moreover, an extended A–π–D–π–A skeleton enables two-photon excitation with the NIR light. One of the derivatives that satisfy these features, i.e., borylethenyl-substituted5, exhibited an intense NIR emission in polar solvents such as acetone ( λ em = 708 nm, Φ F = 0.55) with a strong two-photon-absorption band in the NIR region.